Standardized pressure provocation as an objective clinical marker of omalizumab response in delayed pressure urticaria: an open-label, real-life, prospective cohort - Konstantinou, George N.; Podder, Indrashis (Frontiers in Immunology, 2026)
BackgroundDelayed pressure urticaria (DPU) is a disabling chronic inducible urticaria characterized by delayed painful swelling after sustained pressure. Evidence-based therapeutic options remain limited, and omalizumab is frequently used off-label in antihistamine-refractory cases despite scarce prospective DPU-specific data with objective provocation testing.MethodsIn a prospective, single-center, open-label cohort, adults with dermographometer-confirmed DPU refractory to licensed or high-dose second-generation H1-antihistamines received omalizumab 300 mg subcutaneously every 4 weeks. Patients were contacted daily during the first week after the initial dose and deliberately exposed to their typical pressure triggers to define time to complete symptom control. Baseline clinico-demographic characteristics, laboratory parameters, atopic status and comorbidities were recorded, and potential predictors of time to response were explored by univariate regression.ResultsForty-two patients were included (61.9% female; mean age at diagnosis 46.0 ± 14.0 years). Aeroallergen sensitization was present in 52.4% and clinically documented allergic disease in 26.2%; autoimmune thyroid disease was recorded in 33.3%. The DPU phenotype frequently involved soles and/or palms (54.8%), and angioedema (28.6%) and systemic symptoms (26.2%) were common. After the first omalizumab dose, 41/42 patients (97.6%) achieved complete symptom control within 96 hours (median 24 hours); 57.1% responded within 24 hours and 83.3% within 48 hours. One patient achieved only partial control. No serious adverse events or need for rescue systemic corticosteroids were observed. Time to response was not associated with sex, age, baseline total IgE, aeroallergen sensitization, atopic background, or autoimmune thyroid disease.ConclusionIn dermographometer-confirmed, antihistamine-refractory DPU, omalizumab was associated with a rapid clinical remission in almost all patients, typically within 24–48 hours, independent of baseline IgE and common comorbidities. Standardized pressure provocation testing provides objective confirmation of DPU and a pragmatic approach for diagnosis and real-world monitoring of therapeutic response in DPU. Given the open-label, uncontrolled design, these findings should be confirmed in larger multicenter controlled studies.